Constant elasticity of variance model: An application in the stock market of Lima - Quispe S., Dennis (2022)
The objective of this article is to present the constant elasticity of variance model, its main probabilistic aspects, and we implement the stochastic Runge Kutta method to simulate the sample trajectories based on the data of the CREDITC1 asset of the Bank of Credit from Perú taken from the Lima stock exchange.